P. falciparum and P. vivax Orthologous Coiled-Coil Candidates for a Potential Cross-Protective Vaccine - Ayadi, Imen; Balam, Saidou; Audran, Régine; Bikorimana, Jean-Pierre; Nebie, Issa; Diakité, Mahamadou; Felger, Ingrid; Tanner, Marcel; Spertini, François; Corradin, Giampietro; Arevalo, Myriam; Herrera, Socrates; et al. (Frontiers in Immunology, 2020)
Over the last four decades, significant efforts have been invested to develop vaccines against malaria. Although most efforts are focused on the development of P. falciparum vaccines, the current availability of the parasite genomes, bioinformatics tools, and high throughput systems for both recombinant and synthetic antigen production have helped to accelerate vaccine development against the P. vivax parasite. We have previously in silico identified several P. falciparum and P. vivax proteins containing α-helical coiled-coil motifs that represent novel putative antigens for vaccine development since they are highly immunogenic and have been associated with protection in many in vitro functional assays. Here, we selected five pairs of P. falciparum and P. vivax orthologous peptides to assess their sero-reactivity using plasma samples collected in P. falciparum- endemic African countries. Pf-Pv cross-reactivity was also investigated. The pairs Pf27/Pv27, Pf43/Pv43, and Pf45/Pv45 resulted to be the most promising candidates for a cross-protective vaccine because they showed a high degree of recognition in direct and competition ELISA assays and cross-reactivity with their respective ortholog. The recognition of P. vivax peptides by plasma of P. falciparum infected individuals indicates the existence of a high degree of cross-reactivity between these two Plasmodium species. The design of longer polypeptides combining these epitopes will allow the assessment of their immunogenicity and protective efficacy in animal models.